Moderasi Organization Performance Pengaruh Komunikasi Bipartit Dan Employee Relation Terhadap Kinerja Karyawan Pada Perusahaan Perhotelan - Kamaruddin, Muhammad Junaid; Dwita, Febrisi; Novialumi, Anita (JURNAL ADMINISTRASI KANTOR; Vol 11 No 2 (2023): Jurnal Administrasi Kantor (Desember 2023), 2023)
The purpose of this study was to examine and analyze the influence of organization performance and bipartite communication on employee performance moderated by employee relations. The sample in this study consisted of 160 respondents who were the general public around. Respondent coverage is based on the Hair approach. The data collection technique used simple random sampling by distributing research questionnaires in Google format and then sharing them on social media. The research data processing method uses Smart PLS (Partial Least Square) software which is used for hypothesis testing. The results showed that organization performance had a positive and significant effect on employee relations, bipartite communication had a positive and significant effect on employee relations, employee performance proved to have a significant effect.   Keywords : Organization Performance, Bipartite Communication, Employee Relations, Employee Performance.